2017
DOI: 10.1038/s41598-017-04538-3
|View full text |Cite
|
Sign up to set email alerts
|

Map3k8 controls granulocyte colony-stimulating factor production and neutrophil precursor proliferation in lipopolysaccharide-induced emergency granulopoiesis

Abstract: Map3k8 has been proposed as a useful target for the treatment of inflammatory diseases. We show here that during lipopolysaccharide-induced emergency granulopoiesis, Map3k8 deficiency strongly impairs the increase in circulating mature (Ly6GhighCD11b+) and immature (Ly6GlowCD11b+) neutrophils. After chimaeric bone marrow (BM) transplantation into recipient Map3k8−/− mice, lipopolysaccharide treatment did not increase circulating Ly6GhighCD11b+ cells and strongly decreased circulating Ly6GlowCD11b+ cells. Lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…2f), indicating that endothelial MAPK activation leads to an inflammatory stress response. It is well established that NF-κB signaling plays pivotal roles in driving inflammatory responses, and recent reports indicate that endothelial MAPK activation can lead to inflammation via downstream activation of canonical NF-κB signaling 28,29,31,32 . To verify this possibility, we performed immunoblot analysis on BM-derived ECs (BMECs) of CDH5-MAPK mice which confirmed an increase in MEK1DD driven ERK1/2 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2f), indicating that endothelial MAPK activation leads to an inflammatory stress response. It is well established that NF-κB signaling plays pivotal roles in driving inflammatory responses, and recent reports indicate that endothelial MAPK activation can lead to inflammation via downstream activation of canonical NF-κB signaling 28,29,31,32 . To verify this possibility, we performed immunoblot analysis on BM-derived ECs (BMECs) of CDH5-MAPK mice which confirmed an increase in MEK1DD driven ERK1/2 phosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Prior work from our group has shown that suppression of NF-κB signaling within ECs enhances steady-state hematopoiesis as well as regeneration following myelosuppression, in part by decreasing proinflammatory cytokines 21 . Recent reports suggest that endothelial MAPK likely plays an essential role during inflammatory processes including LPS-induced granulopoiesis and chronic vascular inflammation-associated atherosclerosis 28,29 . Utilizing an ex vivo niche model system, we have previously demonstrated that endothelial MAPK activation drives myeloid-biased differentiation of co-cultured HSCs at the expense of their self-renewal, features that are suggestive of an inflammatory stress 15 .…”
mentioning
confidence: 99%
“…Infections and tissue damage processes that course with inflammation promote a biased BM hematopoiesis towards the myeloid cell lineage, in order to confront the immune distress 18 , 19 . Furthermore, erythroid precursors generated in the BM under these circumstances display a higher apoptosis rate, and their fully differentiated RBC present a lower half-life than normal 20 , 21 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Blood, BM cells and splenocytes were collected as previously described 19 , 40 . The different cell samples (0.5–2 × 10 6 cells) were stained for the indicated surface markers (see Supplemental Table S2 online) for 20 min at room temperature and subsequently washed twice with buffer A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation